ELABORATION OF TASK CONTROL ALGORITHMS WITH PARALLEL COMPUTING IN CLUSTER COMPUTING SYSTEMS - Abdulmajed A. Al-khulaidi; Yury O. Chernyshev (Advanced Engineering Research, 2011)
The optimum problem of the allocation of tasks for executing in the cluster is considered. Task control algorithms are elaborated. The algorithms validation is done in the performance of the transportation problem on the local network cluster. The data obtained permit to judge efficiency of the suggested algorithms.